Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00464-014-3965-0
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of risk factors for postoperative complications after laparoscopic liver resection

Abstract: Postoperative complication rate increases by 60% with each additional operative hour during LLR. Therefore, expected operative time should be assessed before and during LLR, especially when dealing with malignant tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In addition, the majority of conversions occurred during parenchymal transection after considerable operating time. Hence, to improve the postoperative tolerance and limit the negative effects of both conversion and prolonged surgery, a hybrid approach with laparoscopic pedicular dissection and open parenchymal transection using a minilaparotomy through a midline incision facilitated by a hanging manoeuvre could be attractive in the presence of risk factors for conversion. This seems particularly relevant for large lesions, where extraction of the resected specimen may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of conversions occurred during parenchymal transection after considerable operating time. Hence, to improve the postoperative tolerance and limit the negative effects of both conversion and prolonged surgery, a hybrid approach with laparoscopic pedicular dissection and open parenchymal transection using a minilaparotomy through a midline incision facilitated by a hanging manoeuvre could be attractive in the presence of risk factors for conversion. This seems particularly relevant for large lesions, where extraction of the resected specimen may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a positive association between the duration of surgical procedures and complications such as surgical site infection (SSI), venous thromboembolism (VTE), bleeding, hematoma formation, and necrosis has been reported in prospective and retrospective studies across various surgical procedures. [6][7][8][9][10] Similarly, a systematic review by Visser et al 5 identified, categorized, and ranked various patient-and surgery-related risk factors for complications; prolonged operative duration was among the top three surgery-related factors. However, the review by Visser et al only identified six studies that assessed operative duration and its relationship with surgical-related complications; three studies reported a statistically significant association, whereas three studies reported a nonstatistically significant association.…”
Section: Introductionmentioning
confidence: 99%
“…Liver resection is associated with significant mortality and morbidity, due to complications such as post hepatectomy liver failure, blood loss and bile leak, among other general complications. Postoperative complications have a reported prevalence of 4-53%, [5][6][7][8] with morbidity for open liver resections ranging from 22-47% as opposed to 11-15% for laparoscopic resections. [9][10][11][12][13] Asiyanbola et al conducted a review of literature based (n > 7000) versus population based (n > 11 000) mortality rates and found a lower reported mortality rate in publications (2.6%) verses national statistics (4.9%).…”
mentioning
confidence: 99%